2015
DOI: 10.5433/1679-0359.2015v36n3p1369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oleic-linoleic acid and ?-sitosterol to freezing extender of bulls and stallions semen

Abstract: Addition of polyunsaturated fatty acids and/or cholesterol to a freezing diluent can modify the sperm plasma membrane composition, influencing its behavior during cryopreservation, thus, favoring seminal cryoresistance. The present study aimed to evaluate the effects of the addition of oleiclinoleic acid, (OLA); β-sitosterol (β-sit), a plant analog of cholesterol; and OLA + β-sit in combination to a freezing diluent, on the cryopreservation bull and stallion semen. The following variables were analyzed: motili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…This process generates reactive oxygen species that can have pathological effect on the sperms if in excess, or if the balance with available antioxidant defences compromised, resulting in a decrease In viability, motility and increases in DNA damage, morphology defects as well as lipid peroxidation (AMARAL et al, 2013). According to Sampaio et al (2015), there were no differences between treatments in which different concentrations of lipids (oleic-linoleic acid and beta-sitosterol) were used in the freezing dilution of semen from bulls and stallions in terms of mitochondrial activity. Studies of the role of vitamin E in the dilution of epididymis semen have shown that the addition of docosahexaenoic acid (DHA), a component of the omega-3 family associated with vitamin E, causes a decrease in mitochondrial activity, showing the combined activity of vitamin E with polyunsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…This process generates reactive oxygen species that can have pathological effect on the sperms if in excess, or if the balance with available antioxidant defences compromised, resulting in a decrease In viability, motility and increases in DNA damage, morphology defects as well as lipid peroxidation (AMARAL et al, 2013). According to Sampaio et al (2015), there were no differences between treatments in which different concentrations of lipids (oleic-linoleic acid and beta-sitosterol) were used in the freezing dilution of semen from bulls and stallions in terms of mitochondrial activity. Studies of the role of vitamin E in the dilution of epididymis semen have shown that the addition of docosahexaenoic acid (DHA), a component of the omega-3 family associated with vitamin E, causes a decrease in mitochondrial activity, showing the combined activity of vitamin E with polyunsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%